If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(0) + -8y = 24 Multiply 2 * 0 0 + -8y = 24 Anything times zero is zero. 0 + -8y = 24 Remove the zero: -8y = 24 Solving -8y = 24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-8'. y = -3 Simplifying y = -3
| 0.2+6.51+2.03=a | | -8y=2 | | 3y=9x-24 | | -12.5+20.13=W | | x+x+0.56+x+0.56+1.08=10.51 | | c=9.8+(-2.5) | | 2x^2-3xy-5y^2=0 | | y=-12+(-9.6) | | y=1/4(0)-2 | | m/5+5=7/5 | | 2x-3xy-5y=0 | | y=1/4(4)-2 | | (11/12/44/5)-(11/12*44/5) | | 14.75+0.18=k | | 8-5x=4-6x | | 15/48=54 | | 8-1x=4-6x | | -6x^2+5y+6=0 | | 5y^2+34y+24=0 | | 3y^2+15y-18=0 | | 5x^2-7x+3=3x^2-2x | | x^2-14x+18=0 | | 8x+17/13-7x=1/26 | | 992/-32=q | | 3u^3x^4-3u^3= | | 125+10h=230 | | 3v^3-4v^2+9v-12= | | 1/5(x-35)=4/5 | | R=72/-8 | | 125+10h=4b-1 | | 3(x-3)+49=-2x | | 42/6=f |